LIFE CHANCES AND STRUCTURAL INEQUALITY (Glocalism: Journal of Culture, Politics and Innovation, 2024)
The article delves into the historical trajectory of global inequality, tracing the transition from an era of relative equality to the emergence of profound disparities following the Industrial Revolution and the rise of the West. It scrutinizes the Eurocentric narrative of progress, emphasizing the pivotal role of scientific advancements, technological innovations, and capitalist expansion in shaping the Western ascendancy. Furthermore, it explores the concept of life chances as a lens through which to analyse structural inequality and the distribution of resources among individuals. The discourse extends to the revaluation of values in the context of sustainability, advocating for a shift towards a more sustainable and equitable societal framework. The paper underscores the enduring challenges posed by durable inequality and the allure of the Western lifestyle to less privileged regions. Through a multidisciplinary lens encompassing historical, sociological, and ecological perspectives, it offers insights into the complexities of global development, social stratification, and the quest for a more just and sustainable world order.
Keywords: inequality; progress; eurocentrism; life chances; sustainability